International and Interpretive Dimensions - Kotsonis, Yanni (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2016)
The author engages the comments of his colleagues on his book, States of Obligation, and reiterates the international and interpretive dimensions of the monograph.